2019
DOI: 10.3390/molecules24081466
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Process Schemes Combining Hydrothermal Treatment and Acidogenic Fermentation of Source-Separated Organics

Abstract: This study compares the effects of pre- and post-hydrothermal treatment of source- separated organics (SSO) on solubilization of particulate organics and acidogenic fermentation for volatile fatty acids (VFAs) production. The overall COD solubilization and solids removal efficiencies from both schemes were comparable. However, the pre-hydrolysis of SSO followed by acidogenic fermentation resulted in a relatively higher VFA yield of 433 mg/g VSS, which was 18% higher than that of a process scheme with a post-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Temperature has been proven to play a crucial role in sludge disintegration during HTP [20,22,[27][28][29]. It was reported that temperatures above 100 • C improve the sludge disintegration drastically, whereas going beyond 200-220 • C produces refractory compounds such as melanoidins [30][31][32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature has been proven to play a crucial role in sludge disintegration during HTP [20,22,[27][28][29]. It was reported that temperatures above 100 • C improve the sludge disintegration drastically, whereas going beyond 200-220 • C produces refractory compounds such as melanoidins [30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…BMP tests are usually conducted to understand the methane production potential, the methane production rate, and biodegradability [21][22][23]. In the current study, we have used the same procedure and conditions for the BMP test described previously [24].…”
Section: Biochemical Methane Potential (Bmp) Testmentioning
confidence: 99%
“…Regardless of the disintegration method used, the primary effect of the treatment is the liquefaction of the substrate's solid fraction. It is assumed that the fragmentation of sludge or solid waste will increase the availability of organic substances for micro-organisms; i.e., the potential biodegradability [12]. However, the existing literature does not confirm this fact unequivocally.…”
Section: Introductionmentioning
confidence: 99%